Glycyrrhizic acid in the chronic vulvovaginitis and cervicitis treatment - A V Ledina; V N Prilepskaya (IP Berlin A.V., 2013)
Chronic vulvovaginitis and cervicitis are common pathological conditions in obstetrician-gynecologist practice. The main infectious agents, leading to their development are microorganisms and viruses. Causative treatment is carried out by means of the microscopic, microbiological or molecular biological survey methods. Due to changes in local immunity at chronic inflammation of the lower genital tract the use of immuno drugs (interferon and its inducers) is a necessary part of the pathogenetic therapy and is especially effective in treatment of vulvovaginitis associated with viral infection. Here, the data on the positive effect of glycyrrhizin acid complex treatment of chronic cervicitis and benign lesions cervix is presented.